SMS-text messaging for collecting outcome measures after acute stroke - DiCarlo, Julie A.; Erler, Kimberly S.; Petrilli, Marina; Emerson, Kristi; Gochyyev, Perman; Schwamm, Lee H.; Lin, David J. (Frontiers in Digital Health, 2023)
Traditional methods for obtaining outcomes for patients after acute stroke are resource intensive. This study aimed to examine the feasibility, reliability, cost, and acceptability of collecting outcomes after acute stroke with a Short Message Service (SMS)-text messaging program. Patients were enrolled in an SMS-text message program at acute stroke hospitalization discharge. Participants were prompted to complete assessments including the Modified Rankin Scale (mRS) and Patient-Reported Outcomes Measurement (PROM) Information System Global-10, at 30, 60, and 90 days post-discharge via SMS-text. Agreement and cost of SMS-text data collection were compared to those obtained from traditional follow-up methods (via phone or in clinic). Participant satisfaction was surveyed upon program conclusion. Of the 350 patients who agreed to receive SMS-texts, 40.5% responded to one or more assessments. Assessment responders were more likely to have English listed as their preferred language (p=0.009), have a shorter length of hospital stay (p=0.01) and lower NIH Stroke scale upon admission (p<0.001), and be discharged home (p<0.001) as compared to non-responders. Weighted Cohens Kappa revealed the agreement between SMS-text and traditional assessments was almost perfect for dichotomized (good versus poor) (κ=0.8) and ordinal levels of the mRS score (κ=0.8). Polychoric correlations revealed a significant association for PROM scores (ρ=0.4, p<0.01 and, ρ=0.4, p<0.01). A cost equation showed that gathering outcomes via SMS-text would be less costly than phone follow-up for cohorts with more than 181 patients. Nearly all participants (91%) found the program acceptable and not burdensome (94%) and most (53%) felt it was helpful. Post-stroke outcomes data collection via SMS-text is feasible, reliable, low cost, and acceptable. Reliability was higher for functional outcomes as compared to PROMs. While further validation is required, our findings suggest that SMS-texting is a feasible method for gathering outcomes after stroke at scale to evaluate the efficacy of acute stroke treatments.